2012
DOI: 10.1007/s12350-012-9601-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of a normal Tl-201 stress-only SPECT MPI study

Abstract: Normal stress-only Tl-201 SPECT MPI study has a similarly benign prognosis when compared to Tc-99m rest-stress and Tc-99m stress-only normal SPECT MPI studies. The stress-first design allowed for early triage of over 60% of patients and marked improvement in laboratory efficiency due to shortened test time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…35 Numerous studies have demonstrated the value of a normal exercise MPI with a low annual cardiac event rate (\1%) for most patients. 6,31,33,34,36 Even in patients with known CAD, the primary event rate with normal exercise MPI or echocardiography is relatively low. 29,31,32,37 -41 In our study, the CV mortality in the normal MPI group was 0% and the CV mortality plus MI were 1.1%/year after about 4 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…35 Numerous studies have demonstrated the value of a normal exercise MPI with a low annual cardiac event rate (\1%) for most patients. 6,31,33,34,36 Even in patients with known CAD, the primary event rate with normal exercise MPI or echocardiography is relatively low. 29,31,32,37 -41 In our study, the CV mortality in the normal MPI group was 0% and the CV mortality plus MI were 1.1%/year after about 4 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Nessa situação, estudos recentes demonstraram que o valor prognóstico da prova fica mantido, a capacidade diagnóstica semelhante às custas de elevada sensibilidade, bem como o paciente recebe menor dose de atividade radioativa e tem o tempo total de exame diminuído. 32,33 5.3. Cintilografia de Perfusão Miocárdica com Imagens Tomográficas Sincronizadas pelo Eletrocardiograma (Gated-SPECT) [34][35][36][37][38][39][40][41] As imagens cardíacas devem ser adquiridas de maneira sincronizada com o ECG do paciente, permitindo a análise adicional da função ventricular e de forma simultânea a avaliação da perfusão miocárdica.…”
Section: Cintilografia De Perfusão Miocárdica Com Imagens Tomográficaunclassified
“…The new‐generation dedicated cardiac systems enable “stress‐first” SPECT protocols with lower doses and obviate the need for subsequent rest studies if stress studies are normal (~60% of cases) . This has been shown to reduce radiation exposures to patients and associated personnel, but acquisitions take about 10–14 min . Additionally, these new cameras are not yet prevalent, with standard Anger camera‐based systems still used for the vast majority of patients.…”
Section: Introductionmentioning
confidence: 99%